Prevalence of Adverse Events and factors related to accidental loss of invasive devices in an Intensive Care Unit (Research, Society and Development, 2021)
Objective: To characterize the adverse events related to the accidental loss of invasive devices in an intensive care unit. Methodology: This is a retrospective quantitative study. Data from patients admitted to an Intensive Care Unit (ICU), from July 2018 to July 2019, who suffered adverse events was used. Results: The sample consisted of 218 individuals with which adverse events occurred, 62.8% of those being male, with an average age of 59.8 years. This sample of 218 individuals represented, among a total of 882 patients admitted throughout the same period, a prevalence of 24,78%. The occurrence of delirium was prevalent in 33.9% of cases. The average length of hospital stay was 10 days in the ICU and 35 days in the hospitalization sector. Regarding the distribution of adverse events, the highest occurrence was related to accidental loss of enteral tube (49.1%). Of these, 156 events (71.6%) were characterized as without damage and 62 (28.4%) as mild damage, evolving to recovery without sequelae (99.80%). Conclusion: It should be noted that the hospital in question presented a good indicator of quality about accidents caused by invasive devices. However, the improvement of care for patients must be constantly improved, in order to minimize adverse events and strengthen the culture of care.